Communication and information technologies annual - Robinson, Laura (Emerald, 2015)
Sponsored by the Communication, information technologies, and media section of the American Sociological Association, Volume 10 of the Communication and information technologies annual, Digital distinctions and inequalities, brings together nine studies of this increasingly important form of inequality. Drawn from four continents, the research provides a global overview of the current state of the field in different cultural contexts. As a whole, the volume illuminates the complexities of digital inequalities as they are manifested in groups and societies even when access is widespread. In their depth and breadth, the volume's contributions provide an indispensable guide to emergent forms of digital inequality as it rapidly evolves.
Keywords: Social Science -- Media Studies.; Communication studies.; Information technology -- Social aspects.; Information technology -- Political aspects.; elektronické knihy; electronic books